The Evolution of Magnetic Rayleigh-Taylor Unstable Plumes and Hybrid KH-RT Instability into a Loop-like Eruptive Prominence - Mishra, S.K.; Srivastava, A.K. (Institute of Physics Publishing, 2019)
MRT-unstable plumes are observed in a loop-like eruptive prominence using Solar Dynamic Observatory/Atmospheric Imaging Assembly observations. The small-scale cavities are developed within the prominence, where perturbations trigger dark plumes (P1 and P2) propagating with speeds of 35-46 km s -1 . The self-similar plume formation initially shows the growth of a linear MRT-unstable plume (P1), and thereafter the evolution of a nonlinear single-mode MRT-unstable second plume (P2). A differential emission measure analysis shows that plumes are less dense and hotter than the prominence. We have estimated the observational growth rate for both plumes as 1.32 ±0.29 ×10 -3 s -1 and 1.48 ±0.29 ×10 -3 s -1 , respectively, which are comparable to the estimated theoretical growth rate (1.95 ×10 -3 s -1 ). The nonlinear phase of an MRT-unstable plume (P2) may collapse via a Kelvin-Helmholtz vortex formation in the downfalling plasma. Later, a plasma thread is evident in the rising segment of this prominence. It may be associated with the tangled field and Rayleigh-Taylor instability. The tangled field initiates shearing at the prominence-cavity boundary. Due to this shear motion, the plasma downfall occurred at the right part of the prominence-cavity boundary. It triggers the characteristic KH unstable vortices and MRT-unstable plasma bubbles propagating at different speeds and merging with each other. The shear motion and lateral plasma downfall may initiate hybrid KH-RT instability there. © 2019. The American Astronomical Society. All rights reserved..
Keywords: Sun: corona